Improvement of oxidative stress tolerance in Saccharomyces cerevisiae through global transcription machinery engineering. (1st May 2014) - Zhao, Hongwei; Li, Jingyuan; Han, Beizhong; Li, Xuan; Chen, Jingyu
Abstract: Excessive oxidative stress poses significant damage to yeast cells during fermentation process, and finally affects fermentation efficiency and the quality of products. In this paper, global transcription machinery engineering was employed to elicit Saccharomyces cerevisiae phenotypes of higher tolerance against oxidative stress caused by H2 O2 . Two strains from two plasmid-based mutagenesis libraries (Spt15 and Taf25), which exhibited significant increases in oxidative stress tolerance, were successfully isolated. At moderate H2 O2 shock (≤3.5 mM), a positive correlation was found between the outperformance in cell growth of the oxidation-tolerate strains and H2 O2 concentration. Several mutations were observed in the native transcription factors, which resulted in a different transcriptional profile compared with the control. Catalase and superoxide dismutase activities of the two mutants increased under H2 O2 stress conditions. Fermentation experiments revealed that the mutant strain taf25-3 has a shorter lag phase compared to the control one, indicating that taf25-3 had improved adaptation ability to H2 O2 -induced oxidative stress and higher fermentation efficiency. Our study demonstrated that several amino acid substitutions in general transcription factors (Spt15 and Taf25) could modify the cellular oxidation defense systems and improve the anti-oxidation ability of S. cerevisiae . It could make the industrial ethanol fermentation more efficient and cost-effective by using the strain of higher stress tolerance.